Faktor Eksternal Pendorong Invasi Pertanaman Jagung di Wilayah Kesatuan Pengelolaan Hutan Lindung Ampang Plampang, Kabupaten sumbawa - Arief Rachmadi; Taslim Sjah; Hayati Hayati (Universitas Mataram, 2022)
Invasion of corn plantations in the Ampang KPHL area can disrupt not only the function but also the existence of the forest, so it needs to be handled comprehensively. This study aims to determine the external factors driving the invasion of corn plantation in KPHL Ampang. This research is a descriptive research, data and information are extracted through searching the key actors, online and through interviews. Data and information were tabulated and analyzed descriptively. The results show the external factors driving corn plantation in KPHL Ampang, including: Regulatory factors and implementation of regulations at the site level that support the development of corn plantation widely; The attractiveness of business profits from corn plantation; and The ease of obtaining capital assistance, training, market access, and business equipment. In relation to the forest encroachment invasion, the Government needs to consider the impact of a policy across sectors before a policy is implemented. The government also needs to provide guidance, control and assistance to farmers as implementing actors in the field.